ROLE OF FINANCIAL SUBSIDIES ALLOCATED BY THE CAP TOWARDS SLOVENIAN FARMERS - Nicola GALLUZZO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Financial subsidies allocated by the European Union (EU) throughout the Common Agricultural Policy (CAP) have had a positive effect on the rural development in particular in less favoured rural areas. The Farm Accountancy Data Network is an useful tool in order to estimate the impact of payments allocated by the CAP on the farm net income in a sample of European farms. Before of European Union enlargement in 2004 Slovenian farmers have benefited of specific initiatives aimed at implementing the productive agrarian fabric. Findings have pointed out as financial subsidies allocated towards stayed behind rural areas have been indirectly correlated to the dependent variable farm net income, even if the usable agricultural surface is one of the most important variable acting predominately towards the level of farmer’s income and economic efficiency.